Knee arthrodesis as last resort for persistent knee joint infections: Comparison of extramedullary and intramedullary treatment - Zajonz, Dirk (Orthopade, 2020)
BACKGROUND: Knee joint arthrodesis is an established treatment for periprosthetic infections (PPI) providing stability and pain relief. In this study the outcome after arthrodesis of the knee joint for persistent infections was compared and evaluated depending on the surgical procedure (intramedullary vs. extramedullary). MATERIAL AND METHODS: In a retrospective case analysis, all patients who underwent knee joint arthrodesis between 1 January 2010 and 31 December 2016 were identified and divided into two groups: IMA and EMA. All patients were examined clinically and radiologically and the patient files were evaluated. In addition, the FIM score, the LEFS, the WHOQOL-BREF and NRS were evaluated. RESULTS: The median LEFS score for the IMA group was 26 points and in the EMA group 2 points (p = 0.03). The IMA patients showed a median pain scale at rest of 0 and during exercise of 2. The EMA group recorded a pain scale of 3 at rest and 5 during exercise (p = 0.28 at rest; p = 0.43 during exercise). In the IMA group the median postsurgical leg length difference was −2.0 cm and −2.5 cm in the EMA group (p = 0.31). At the end of the follow-up examinations, the FIM score of patients in the IMA group was 74.5 points and 22 points in the EMA group (p = 0.07). CONCLUSION: The study showed that no arthrodesis procedure is obviously superior with respect to the postoperative outcome. The IMA combines advantages especially in the early phase after surgery in terms of function as well as patient comfort and is therefore currently the procedure of choice. The attending physician should be familiar with the advantages and disadvantages of the various procedures in order to be able to make an individual decision and thus maximize the chance of treatment success.